Stabilising fragile democracies : comparing new party systems in Southern and Eastern Europe - Pridham, Geoffrey, 1942-; Lewis, Paul G., 1945- (Routledge, 1996)
"This book provides a systematic comparison of the democratic transition in both southern and eastern Europe. The role of the parties is a crucial determinant as to whether a new democracy will put down deep and long-lasting roots. The book is directed towards four main themes - 'coping with the past' (party identities and inheritances); the formation and performance of new democratic political elites; parties and alliances/coalitions; and their electoral behaviour. These themes are discussed comparatively with the aid of four case studies from both southern and eastern Europe. The countries covered include Italy, Spain, Greece, Portugal, Hungary, Romania, Poland and Bulgaria." "Democratisation is a very complex process because it operates on so many levels, but by studying political parties you can focus on an area that covers many of them. Students of European politics will find this an invaluable guide to recent events in eastern Europe as well as a means to understanding the process of democratisation more generally."--BOOK JACKET.